Enhancing Students’ Creative Thinking Skills through Biotechnology Module based Socio-Scientific Issues - Indarini Dwi Pursitasari; Nia Alfitriyani; Surti Kurniasih (Postgraduate, University of Mataram, 2022)
This study aims to enhance students’ creative thinking skills through the biotechnology module based on socio-scientific issues. This is pre-experimental research with a one-group pretest-posttest design. The learning is carried out online using the Zoom meeting application, which is familiar to the students. The instrument for collecting data is a valid creative thinking skill test sheet. The students’ responses were analyzed using a questionnaire. The data analysis was done by descriptive quantitative and inferential. The result of the inferential statistical test shows that there is a significant effect of using SSI-based biotechnology modules on students’ creative thinking skills. The SSI-based biotechnology module is effective to improve creative thinking skills, indicated by the N-Gain value is 0.63 in the moderate category. The learning implementation has an average value above 75%, indicating that the learning process is carried out very well. 87.50% of the students gave excellent responses to the use of the SSI-based module in learning. There is an increase in the N-Gain value in creative thinking skills, so we can conclude that the biotechnology module based on the socio-scientific issue is effective to improve creative thinking skills